Effect of stress distribution on transverse and longitudinal framing in cargo ship using FEA method - Zakaria, Z.A.B. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
A cargo shipâs hull is made up of bent plates that are not stiffened. The hull can be strengthened by the structural member of the transverse or longitudinal framing system. Frames are strengths member that acts as integral parts of the ship girder when the ship exposed to the longitudinal and transverse stresses. One of the stresses is coming from the load by the container that the cargo ships carry. This research was conducted to analyse how the load does from the container affecting the total deformation and the stress distribution on the transverse framing system model. The analysis of model was using finite element analysis method. Finite element analysis is a numerical technique for solving engineering issues with complex loadings, geometries and material properties. The simulation results of equivalent (von-Mises) stress and total deformation will be compared with the Germanisher Lloyd rule. The result of total deformation and equivalent (von-Mises) stress must not exceed the value stated by Germanischer Lloyd rule. If the value of stress exceeds, it is considered a failure. All the results are not exceed the limit and is acceptable. Â© BEIESP.